Pelestarian Seni Tradisional Randai sebagai Upaya Penguatan Identitas Budaya Lokal di Masyarakat - Hermansyah Hermansyah; Hikmahtul Indra; Dea Nabilah; Rani Khairunnisa; Alya Resti Andesva; Zahir Fikri Rashief Azwar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Randai traditional art is one of the cultural heritages of Minangkabau that holds significant aesthetic, educational, and social values; however, its existence is increasingly threatened due to globalization and the declining interest of the younger generation. The lack of attention and limited preservation efforts are the main factors contributing to the decline of this traditional art. Therefore, concrete efforts are needed to preserve randai as part of local cultural identity. This article aims to examine the preservation of randai as an effort to strengthen cultural identity through the Community Service Program (KKN) using a participatory approach involving students and the community in activities such as socialization, training, and performances. The results indicate that these activities can increase public awareness of the importance of local culture and revive the interest of the younger generation in learning and preserving randai. Furthermore, the program also strengthens social cohesion and cultural identity within the community. In conclusion, the preservation of randai not only serves to maintain cultural heritage but also acts as a means of strengthening local cultural identity in the midst of modernization.